THE USE OF QQ IN EFL TEACHING AND LEARNING: A LITERATURE REVIEW - Yang, LEI; MAREŠOVÁ, Hana (Trends in education, 2018)
Tencent QQ is considered to be one of the most popular instant messaging software in China. It has been widely used to facilitate teaching and learning. This research aims to give a general picture about the researches concerning the use of QQ in EFL teaching and learning, and tries to find the questions asked, the methods used and the answers found by Chinese researchers. 224 articles have been retrieved from CNKI, the largest academic database in China, and processed according to publication information, research questions, methods, results and their relatedness to QQ and to the use of QQ in EFL teaching and learning. Existing researches mainly focus on the use of QQ in EFL teaching, learning and QQ-based communication. Qualitative, quantitative and integrated methods are used respectively. It has been repeatedly proved that QQ can have positive effects on various levels, forms and fields of EFL teaching and learning. In the future, researches can adopt social, cultural, humanistic or cross-disciplinary perspectives and focus on 1) the theory of using QQ, 2) the use of QQ in primary and secondary education, 3) the use of QQ in reading, listening, speaking and translation, 4) the use of QQ affected by contextual and individual factors, 5) the risks of using QQ, 6) the relationship between the use of QQ and other technologies, and 7) the relationship between QQ-based teaching and other teaching approaches.
Keywords: QQ; EFL; teaching; learning; communication